2021
DOI: 10.21203/rs.2.20165/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral Sensitization Induced by Methamphetamine Causes Differential Alterations in Gene Expression and Histone Acetylation of the Prefrontal Cortex in Rats

Abstract: Background: Methamphetamine (METH) is one of the most widely abused illicit substances worldwide; unfortunately, its addiction mechanism remains unclear. Based on accumulating evidence, changes in gene expression and chromatin modifications might be related to the persistent effects of METH on the brain. In the present study, we took advantage of METH-induced behavioral sensitization as an animal model that reflects some aspects of drug addiction and examined the changes in gene expression and histone acetylat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Additionally, we have conducted some experiments to analyze possible methamphetamine-induced epigenetic changes, and results indicated that methamphetamine intake was correlated with an increased amount of DNA methylation and associated gene repression. Similar results have been documented for methamphetamine-induced addiction studies in other animal models (27,28). While hypermethylation could possibly be associated with the upregulation of ion channel genes and the subsequent dysregulation of cardiac rhythm, the exact mechanism linking these epigenetic and physiological changes remains unknown.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, we have conducted some experiments to analyze possible methamphetamine-induced epigenetic changes, and results indicated that methamphetamine intake was correlated with an increased amount of DNA methylation and associated gene repression. Similar results have been documented for methamphetamine-induced addiction studies in other animal models (27,28). While hypermethylation could possibly be associated with the upregulation of ion channel genes and the subsequent dysregulation of cardiac rhythm, the exact mechanism linking these epigenetic and physiological changes remains unknown.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous studies, we found that subthreshold dose of METH (METH F1 ), which is insufficient to induce CPP in naï ve mice, effectively induced METH-preferred behaviors in METH-sired male F1 and not in SAL-sired male F1, indicating an enhanced sensitivities to drugs in F1 of sires exposed to METH. The mPFC has been implicated in the vulnerability to drug abuse [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study found that METH-sired rats exhibit more sensitized behaviors in response to acute drug use [3], indicating that paternal METH use may enhance susceptibility to drugs in offspring. The medial prefrontal cortex (mPFC) is critically implicated in the processes of METH addiction [4,5] and susceptibility to drugs [6][7][8]. Human imaging studies show that prenatal METH exposure significantly affect the volume, cortical thickness and connection of offspring brains, especially the prefrontal cortex (PFC) [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation